SYNTHESIS, ANTIBACTERIAL, ANTIFUNGAL ANTITUBERCULAR ACTIVITIES AND MOLECULAR DOCKING STUDIES OF NITROPHENYL DERIVATIVES: Pharmaceutical Science-Pharmaceutical Chemistry - SURENDRA BABU, LAGU; PRASAD, Y. RAJENDRA; NISSANKARARAO, SRINATH; BASHA SHAIK, AFZAL (International Journal of Life Science and Pharma Research, 2019)
Infectious diseases are one of the common problems encountered globally. Even though there are a number of drugs available in the market for the treatment of infectious diseases, still many new molecules are required due to the problems with the existing drugs. Hence we prepared a series of chalcones (A1-A10) containing nitrophenyl moieties by Claisen-Schmidt condensation reaction. All the ten compounds were characterized by IR, NMR, Mass spectroscopy and elemental analysis. The compounds were further screened for antitubercular activity employing MABA assay and antibacterial and antifungal activities by cup plate method against selected tubercular, bacterial and fungal organisms. The compound A9 displayed potent antitubercular activity with MIC 11.02±0.030, whereas the compound A3 showed superior antibacterial and antifungal activities. Further, molecular docking studies were performed on Thymidine Kinase (TMP) of Mycobacterium tuberculosis by employing AU autodocker. The docking scores were in association with the in vitro MABA results and also identified the potent nature of A9 with the docking score -6.7. This study helped to identify novel nitrophenyl derivatives against thymidylate kinase.